Applying evolutionary anthropology. Issue 1 (2nd January 2015) - Gibson, Mhairi A.; Lawson, David W.
<x xml:space="preserve">Abstract</x> Evolutionary anthropology provides a powerful theoretical framework for understanding how both current environments and legacies of past selection shape human behavioral diversity. This integrative and pluralistic field, combining ethnographic, demographic, and sociological methods, has provided new insights into the ultimate forces and proximate pathways that guide human adaptation and variation. Here, we present the argument that evolutionary anthropological studies of human behavior also hold great, largely untapped, potential to guide the design, implementation, and evaluation of social and public health policy. Focusing on the key anthropological themes of reproduction, production, and distribution we highlight classic and recent research demonstrating the value of an evolutionary perspective to improving human well‐being. The challenge now comes in transforming relevance into action and, for that, evolutionary behavioral anthropologists will need to forge deeper connections with other applied social scientists and policy‐makers. We are hopeful that these developments are underway and that, with the current tide of enthusiasm for evidence‐based approaches to policy, evolutionary anthropology is well positioned to make a strong contribution.